The Role of Hadith in Shaping Digital Spirituality: An Analysis of Texts on Controlling the Gaze and the Heart - Wardani, Retno Endah Kusuma; Nasrulloh, Nasrulloh (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
This article examines the role of Prophetic hadith in shaping digital spirituality, with a specific focus on the ethical principles of controlling the gaze and safeguarding the heart in the online environment. The increasing of visual and distraction-driven nature of digital culture has created significant challenges for Muslim spiritual life, including weakened self-regulation, loss of attentiveness, and heightened exposure to morally harmful content. This study aims to explore how selected hadiths concern about lowering the gaze (ghaḍḍ al-baṣar) and the purification of the heart can offer a relevant ethical-spiritual framework for navigating digital spaces. Using a qualitative library research method with a thematic (mauḍū‘ī) and semantic (ma‘ānī al-ḥadīth) approach, this article analyzes foundational texts and their classical commentaries to uncover their contemporary implications. The findings indicate that the Prophetic teachings on visual discipline, inner vigilance, and heart-centered consciousness provide practical guidance for resisting digital overstimulation, maintaining moral clarity, and cultivating spiritual presence. This study concludes that recontextualizing hadith within the dynamics of digital life contributes to the formulation of digital spirituality that is ethically grounded, psychologically stabilizing, and spiritually transformative.